The Issue on eTravel Business: The Impact of Poor Digital Media Design 2013; A Case of Thailand (Global Journal of Management and Business Research, 2018)
This research investigates the cause of revenue deceleration in eTravel in Thailand about the design of digital media eTravel involves the purchasing activities of customers for example in online travel service booking and online ticketing These services are provided by businesses with an online presence known as eTravel service providers The quantitative research approach determines the relationship between satisfaction factors in digital media design and conversion The reasons for failure in eTravel conversion are presented as association rules The research results are used as inputs for developing digital media design guidelines-for example in recommendations for website design to engage more customers and result in conversions By applying the guidelines on digital media design the local eTravel service provider can successfully increase eTravel revenue In this study eTravel increased in revenue by 42 50 on average compared to the same month in the previous year This confirms the applicability of the proposed guidelines
Keywords: digital media design; etravel; conversion; customer satisfaction; association rules